Vestire i panni di un altro: l’empatia dell’attore nei confronti del personaggio - Julia Gallagher, Shaun Gallagher (Bollettino Filosofico, 2022)
What does it mean for an actor to empathize with the character she is playing? We review different theories of empathy and of acting. We then consider the notion of “twofoldness” (Wollheim), which has been used to characterize the observer or audience perspective on the relation between actor and character (Smith). This same kind of twofoldness or double attunement applies from the perspective of the actor herself who must, at certain points of preparation, distinguish between the character portrayed and her own portrayal effected in her craft. We argue that this concept helps us to understand how the actor can empathize with her character. For the actor who must study and rehearse her character, empathy may begin with higher-order (narrative or imaginative) processes that provide a contextualized understanding of the character. This understanding eventually integrates with more basic empathic processes in her actual performance. Keywords: Acting, Character, Empathy, Imagination, Narrative, Twofoldness